THE EFFECTIVENESS OF MEDIA INSTAGRAM TOWARD THE STUDENTS SPEAKING SKILLS AT ISLAMIC INSTITUTE SUNAN KALIJOGO MALANG - Zizi Nurhikmah (Language-Edu, 2021)
The use of online learning brings many changes to teach EFL in Indonesia. The teacher should be creative in making a medium to make the students interested in and enjoyed the lesson. The purpose of this study is to know how to use Instagram as a medium for teaching students' speaking skills and students’ response toward the treatment of Instagram. This study used Classroom Action Research (CAR) with two cycles. It involved 27 Islamic Preaching and Communication students of Institute Sunan Kalijogo Malang.  In the treatment process, the students were asked to make some videos of some chosen topics. The students were asked to fill in the questionnaires of the Instagram implementation. Based on the result of the data analysis, it was concluded that students had improved their speaking skills and given positive responses through the use of Instagram as a medium in learning English.